Salafism, State Recognition and Local Tension: New Trends in Islamic Education in Lombok - Saparudin Saparudin (Ulumuna, 2017)
This paper explores the role of Salafi formal schools in the increasing influence and proliferation of Salafism in Lombok, East Indonesia, alongside the impacts of this process on educational culture and broader social contexts. Despite intense resistance from, and even violence by, traditionalist mainstream groups, the Salafi movement has developed steadily. This paper argues that the growth of Salafism in Lombok is influenced by contextualizing of proliferation strategies by integrating into Indonesian national education system and selecting of the greater Islamic traditions, rather than ideological and financial support from the Middle East, as it has been highlighted in previous studies and literature. By establishing officially certified schools and formal recognitions from the Indonesian government, the Salafi schools have found a way to successfully recruit a new young generation of Muslims in Lombok and beyond.